2003
DOI: 10.1113/jphysiol.2003.040501
|View full text |Cite
|
Sign up to set email alerts
|

The Electrophysiological Properties of Spontaneously Beating Pacemaker Cells Isolated from Mouse Sinoatrial Node

Abstract: In order to examine the phenotypic consequences of genetic manipulation in the function of the sinoatrial (SA) node, it is a prerequisite to record the electrical activities of a single pacemaker cell of the SA node of mouse heart. In the present study, we isolated spontaneously beating pacemaker cells from the SA node by enzymatic digestion. The rate of spontaneous action potential firing was 294 ± 59 min−1 at 33–34 °C. The maximal diastolic potential (MDP) was −56.7 ± 7.4 mV and the overshoot was 22.7 ± 6.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
90
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 42 publications
11
90
0
1
Order By: Relevance
“…Typical pacemaker cells of the porcine SAN are morphologically similar to those of other species (Irisawa et al, 1993;Ono et al, 2000;Ono and Ito, 1995;Cho et al, 2003). They were visually identified as long, spindle shaped cells in control Tyrode's solution.…”
Section: Morphology and Action Potentialmentioning
confidence: 68%
See 1 more Smart Citation
“…Typical pacemaker cells of the porcine SAN are morphologically similar to those of other species (Irisawa et al, 1993;Ono et al, 2000;Ono and Ito, 1995;Cho et al, 2003). They were visually identified as long, spindle shaped cells in control Tyrode's solution.…”
Section: Morphology and Action Potentialmentioning
confidence: 68%
“…It has been reported that IKr exists in SAN cells of a small species such as the rabbit Ono and Ito, 1995;Verheijck et al, 1995), guinea-pig (Anumonwo et al, 1992;Guo et al, 1997) and mouse (Cho et al, 2003), and that it plays an important role in repolarization and the resulting slow diastolic depolarization. Although IKr was not recorded in porcine SAN cells that showed little evidence of striations, it did exist in large, rod-shaped quiescent cells in the same preparations (Ono and Iijima, unpublished data).…”
Section: The Delayed Rectifier K + Current In Porcine San Cellsmentioning
confidence: 99%
“…Not only do these patients exhibit prolonged QT intervals, causing arrhythmias during exercise due to prolonged repolarization in ventricular tissue, they also have a diminished increase in heart rate upon exercise (Haapalahti et al, 2006). No I Ks has been found in mouse SA node (Cho et al, 2003), and, as expected, KCNQ1 knock out mice do not show prolongation of cycle length (Knollmann et al, 2004). Since I Ks is the only I K present in pig, spontaneous activity ceased on blocking I Ks with chromanol 293B (Ono et al, 2000).…”
Section: Slow Component Of the Delayed Rectifier Kmentioning
confidence: 99%
“…Consequently, I K1 will stabilize the membrane potential around E K . This current, which at first glance appears to antagonize spontaneous activity, is not present in rabbit SA node (Irisawa et al, 1993), and is negligibly small in murine and rat SA node cells (Cho et al, 2003;Shinagawa et al, 2000). Figure 4A, right panel, shows typical current traces in a rabbit SA node cell measured with a similar voltage clamp protocol and solutions as in the ventricular myocyte (left panel).…”
Section: Inward Rectifier Kmentioning
confidence: 99%
See 1 more Smart Citation